Therapeutic Intervention in Cancer by Isoliquiritigenin from Licorice: A Natural Antioxidant and Redox Regulator - Zhu Zhang; Ken Kin-Lam Yung; Joshua Ka-Shun Ko (MDPI AG, 2022)
Oxidative stress could lead to a variety of body dysfunctions, including neurodegeneration and cancer, which are closely associated with intracellular signal transducers such as reactive oxygen species (ROS). It has been suggested that ROS is the upstream regulator of autophagy, and that it provides a negative feedback regulation to remove oxidative damage. Defects in the ROS-autophagic redox homeostasis could lead to the increased production of ROS and the accumulation of damaged organelles that in turn promote metabolic reprogramming and induce tumorigenesis. One significant characteristic of pancreatic cancer is the reprogramming of cellular energy metabolism, which facilitates the rapid growth, invasiveness, and the survival of cancer cells. Thus, the rectification of metabolic dysfunction is essential in therapeutic cancer targeting. Isoliquiritigenin (ISL) is a chalcone obtained from the plant Glycyrrhiza glabra, which is a powdered root licorice that has been consumed for centuries in different regions of the world. ISL is known to be a natural antioxidant that possesses diversified functions, including redox regulation in cells. This review contains discussions on the herbal source, biological properties, and anticancer potential of ISL. This is the first time that the anticancer activities of ISL in pancreatic cancer has been elucidated, with a coverage of the involvement of antioxidation, metabolic redox regulation, and autophagy in pancreatic cancer development. Furthermore, some remarks on related compounds of the isoflavonoid biosynthetic pathway of ISL will also be discussed.